Vulvar Reconstruction Using Keystone Flaps Based on the Perforators of Three Arteries - Lee, Yunjae; Lee, Sanghun; Lee, Dongkyu; Yeo, Hyeonjung; Park, Hannara; Park, Hyochun (Archives of Plastic Surgery, 2022)
Various flaps are used to reconstruct skin and soft tissue defects of the vulva following resection of malignancies. Whenever possible, reconstruction using local flaps is the standard treatment. Here, we describe vulvar defect reconstruction using keystone flaps. Standard keystone flaps are based on randomly located vascular perforators. However, we designed a keystone flap that includes perforators of three named arteries (the anterior labial artery of the external pudendal artery, cutaneous branches of the obturator artery, and posterior labial artery of the internal pudendal artery) and the pudendal nerve, which accompanies the internal pudendal artery. Four patients with squamous cell carcinoma and extramammary Paget's disease of the vulva underwent radical vulvectomy and keystone flaps including perforators of three arteries. Depending on the morphology of the defects, keystone flaps were used with different designs. For elliptical and unilateral vulvar defects, a standard keystone flap was designed, and for defects on both sides of the vulva, a double opposing keystone flap was used. For oval defects, the omega variant keystone flap was designed, and when the morphology of the defect needed rotation of the flap, a rotational keystone flap was designed. All the patients showed good function and sensation, with an acceptable cosmetic appearance.
Keywords: surgical procedures; local flap; artery; perineum; vulva